2015
DOI: 10.4172/2329-9096.1000281
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Determinants of Longer Length of Stay on a Canadian Stroke Inpatient Rehabilitation Unit

Abstract: Objective: The relationship between availability of psychosocial resources and inpatient stroke rehabilitation length of stay (LOS) has been inadequately studied. The purpose of this prospective observational study was to identify psychosocial determinants that prolong LOS of patients in a stroke rehabilitation program. Methods: Patients admitted to a multidisciplinary inpatient stroke rehabilitation program in southern Ontario, Canada, were consecutively recruited from October 2008 to August 2010. Patients di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Thus, our findings may not be generalizable to rehabilitation facilities in countries where LOS is significantly shorter. Nevertheless, a recent study in southern Ontario, Canada, involving n = 117 patients reported a median LOS of 45 days [ 19 ] quite similar to our moderate–RPG patients.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Thus, our findings may not be generalizable to rehabilitation facilities in countries where LOS is significantly shorter. Nevertheless, a recent study in southern Ontario, Canada, involving n = 117 patients reported a median LOS of 45 days [ 19 ] quite similar to our moderate–RPG patients.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have mostly focused on investigating the prediction of LOS within the full severity spectrum of stroke rehabilitation patients. Such studies involved a wide range of number of participants, e.g., n = 586, [ 29 ] n = 11,983, [ 2 ] n = 117, [ 19 ] n = 3839, [ 30 ] n = 151, [ 31 ] n = 165, [ 23 ] n = 353. [ 32 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations